Android-Based Porang Cultivation Application Design for North Lombok District Porang Farmers - Raphael Bianco Huwae; Andy Hidayat Jatmika; Moh. Ali Albar; Ahmad Zafrullah Mardiansyah; Noor Alamsyah (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2024)
Porang is a plant that has the potential to be developed as an export commodity as a food ingredient or industrial ingredient (i.e., food, cosmetics, medicine, or health). North lombok regency location is one of the districts in ntb that currently has potential for developing porang farming businesses. Porang farming is currently carried out in 2 subdistricts, namely gangga and bayan, and has 800 farmer members with a land area of 1000 ha. Having an android-based application will help with the management of farmer administration. Based on the results of black-box testing, all features were confirmed to function properly. Additionally, the System Usability Scale (SUS) evaluation involving 30 users yielded an average score of 74.16, placing it within the acceptable category).